Influence of Hormonal Changes on Audiologic Examination in Normal Ovarian Cycle Females: An Analytic Study - Adriztina, Indri; Adnan, Adlin; Adenin, Ichwanul; Haryuna, Siti Hajar; Sarumpaet, Sorimuda (International Archives of Otorhinolaryngology, 2016)
Introduction There is only limited information from previous studies that suggest that auditory function may be influenced by hormones. Recent advances in the field have exposed the potential role of hormones in modulating the auditory system.Objective This study aims to investigate the relationship between menstrual cycle and outer hair cell function with audiological examination.Methods This is an analytic study with a cross-sectional design. The sampling was a systematic random sampling. We found 49 women with normal menstrual cycle and collected their data through interviews, physical examination, and examination of the ear, with otoscopic and other routine otorhinolaryngology examinations. We evaluated Tympanometry, distortion-product otoacoustic emissions (DPOAE), and pure tone audiometry.Results We found the audiometric threshold worse in the follicular phase than other phases at 4000 Hz of the right ear, and in the ovulation was found best than any other phases at 1000 Hz of the left ear with significant difference. We found significant difference of DPOAE between ovulation time and follicular phase at 3000 Hz and 1000 Hz in the left ear and between ovulation and luteal phased at 2000 Hz, 3000 Hz and 5000 Hz in the right ear and at 1000 Hz in the left ear with p < 0.05.Conclusion The result of this study showed that only a small part of audiometry threshold had a significant difference between each menstrual phase. In other words, we found no correlation between menstrual and audiometry threshold. Nonetheless, there is a correlation between menstrual cycle phase and DPOAE amplitude.
Keywords: menstrual cycle; ovulation; luteal phase; follicular phase; DPOAE